2012
DOI: 10.1111/j.1600-048x.2011.05376.x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of an expanding passerine at the distribution margin

Abstract: Individuals may be maladapted to novel environments at the species' distribution margin. We investigated population dynamics in a marginal habitat where reproduction has been proven poor. Survival, population growth rate (l) and its components, breeding and natal dispersal were studied in great tits Parus major breeding at the northern margin of its distribution in northern Finland. We used long term capture-mark-recapture data sets. Study area size and population density were used to explain adult survival ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Despite recent demographic studies suggesting that the northern population is a ‘sink’ (Karvonen et al ., ), Broggi et al . () showed that northern great tits locally adapt their winter metabolism.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite recent demographic studies suggesting that the northern population is a ‘sink’ (Karvonen et al ., ), Broggi et al . () showed that northern great tits locally adapt their winter metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, birds from the southern population may be released from the selective pressure for high insulation capacity, and therefore grow an adequate plumage adapted to milder winter conditions. Despite recent demographic studies suggesting that the northern population is a 'sink' (Karvonen et al, 2012), Broggi et al (2005) showed that northern great tits locally adapt their winter metabolism. However, they appear to be unable to develop a highly insulative plumage structure in line with previous Feather structure data from the central and northern populations from Broggi et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, possible that cold temperatures limit success of great tits wintering in northern conditions by increasing mortality (Järvinen 1983 ). This conjecture is supported by an effect of winter temperature on annual survival (Perdeck et al 2000 ) and the lower survival of breeding great tits in the north (0.38; Karvonen et al 2012 ) compared to sympatric willow tits (0.59; Lampila et al 2006 ) but also compared to great tits breeding in Central and Southern Europe (ca. 0.5; Payevsky 2006 ).…”
Section: Discussionmentioning
confidence: 96%
“…The colonization of new areas by a bird species through natural expansion of the breeding range, from the arrival of the first individuals to the establishment of a population, is fundamental for our understanding of avian speciation and population ecology in general, and of the effects of human activities and climate change in particular (Newton 2003). Still, the mechanisms behind such expansions are poorly known, mainly because such events are rarely directly observed in detail (Karvonen et al 2012). These mechanisms may be intricate, as revealed for the cyclic replacement of one cavity nester by another in ephemeral habitat created by forest fire in Montana, USA; of the rapidly dispersing but poorly competitive Mountain Bluebird (Sialia currucoides) by the slowly dispersing but more competitive Western Bluebird (Sialia mexicana) (Duckworth and Badyaev 2007).…”
Section: Introductionmentioning
confidence: 99%